Association of prescribed oral stimulants on cocaine use among patients enrolled in opioid agonist treatment: A retrospective longitudinal cohort study - Tatangelo, Mark; Tahsin, Farah; Morin, Kristen A.; Marsh, David C. (Frontiers in Psychiatry, 2022)
Objectives The objective of this study was to measure the association of prescribed oral stimulants with the consumption of cocaine among a population of patients receiving Opioid Agonist Therapy (OAT). Methods The study was a retrospective clinical cohort study using the medical records of all patients receiving OAT who attended treatment clinics within the Canadian Addiction Treatment Centers (CATC) in Ontario from April 2014 to February 2021. Linear mixed-effects models were fit for the exposure of prescribed oral stimulants, and the outcome of a positive urinalysis drug screen for cocaine. Covariates for age, sex, and a random effect for patients were fitted to account for differences between and within patient observations over time. Results Among patients receiving OAT therapy n = 314 patients were prescribed oral stimulants and n = 11,879 patients were not prescribed oral stimulants among Ontario CATC clinics (n = 92, n = 145 physicians), the mean age at enrollment for patients receiving oral stimulants was 37.0, SD = 8.8, with 43.6% female patients and for patients not receiving oral stimulants mean age was 36.6, SD = 10.7, with 39.6% female patients. Linear mixed effects models showed no difference in cocaine-positive urine tests over time for fixed effects B = 0.001, however, when considering the Interclass correlation coefficient (ICC) between the fixed effects, we found that time since the prescription of an oral stimulant was associated with a decrease of ICC = −0.14 in cocaine positive urine tests. Increasing age at prescription ICC = −0.92, and being male ICC = −0.23 were associated with decreasing cocaine-positive urine. Conclusion The use of oral stimulant prescriptions to treat cocaine use had no clinically significant benefit in a real-world setting. Patients who receive prescriptions for oral stimulants consume more cocaine before and after treatment compared to patients without an oral stimulant prescription. We also observed that cocaine use was reduced with increased time since treatment initiation.